This answer is restricted. Please login to view the answer of this question.

Login NowHere, Given

f(x, y) = 2x + y

y(0) = 1

x0 = 0 and y0 = 1

Step-size (h) = 0.1

x_{1} = x0 + h = 0.1

x_{2} = 0.2

x_{3} = 0.3

x_{4} = 0.4

We know by Euler’s method

y(x_{i} + 1) = y(x_{i}) + h(f(x_{i} , y_{i}))

**Step 1:**

y(x1) = y(x0) + hf(x0, y0)

y(0.1) = y(0) + hf(0.1)

= 1 + 0.1 x 1

= 1.1

(x1, y1) = (0.1, 1.1)

**Step 2:**

y(x2) = y(x1) + hf(x1, y1)

y(0.2) = y(o.1) + 0.1 f(0.1, 1.1)

= 1.1 + 0.1 x 1.2

= 1.1 + 1.13

= 1.23

(x2, y2) = (0.2, 1.23)

**Step 3:**

y(x3) = y(x2) + hf(x2, y2)

y(0.3) = y(0.2) + 0.1 f(0.2, 1.23)

= 1.23 + 0.1 x (2 x 0.2 + 1.23)

= 1.303

(x3, y3) = (0.3, 1.393)

**Step 4:**

y(x4) = y(x3) + hf(x3, y3)

y(0.4) = y(0.3) + 0.1 x (2 x 0.3 + 1.393)

= 1.393 + 0.1 (2 x 0.3 + 1.393)

= 1.5923

Thus y(0.4) = 1.5923

If you found any type of error on the answer then please mention on the comment or report an answer or submit your new answer.

Click here to submit your answer.

HAMROCSIT.COM

## Discussion